Adenosine and adenosine receptors: a “double-edged sword” in cardiovascular system - Qian, Yongqi; Zheng, Yixuan; Leng, Liang; Liu, Qingqing; Tian, Xiaojuan; Chen, Shilin; Zhang, Sanyin; Xie, Jiang (Frontiers in Pharmacology, 2025)
Adenosine serves a variety of biological purposes in the circulatory system and was first discovered in the heart in 1929. By interacting with four adenosine receptor (AR) subtypes of G protein-coupled receptors—A1AR, A2aAR, A2bAR, and A3AR—adenosine controls physiological processes. In pathological situations, spikes in adenosine activate the four receptor subtypes and alter downstream pathways by altering the generation of cyclic adenosine monophosphate, which contributes to autophagy and inflammation. There will inevitably be conflicting reactions from the various subtypes in this situation. Additionally, via mediating distinct signals or under various models and pathophysiological situations, the same subtype itself may have contradictory effects. Taken together, ARs’ conflicting regulatory roles in the cardiovascular system not only highlight the intricacy of their physiological roles but also offer a crucial avenue for future study into the treatment of cardiovascular diseases. The contradictory regulatory roles of adenosine and ARs in cardiovascular disorders, as well as their potential as therapeutic targets, are methodically outlined in this review.